Aloe vera mouthwashes can be a natural alternative to chemically formulated ones – A randomized-controlled trial - Naina Pattnaik, MDS; Rinkee Mohanty, MDS; Anurag Satpathy, MDS; Rashmita Nayak, MDS; Rohina Shamim, MDS; Ashok K Praharaj, MD (Journal of Taibah University Medical Sciences, 2022)
الملخص: أهداف البحث: تقييم الفعالية المضادة للبكتيريا والترسبات لغسول الفم المتاح تجاريًا المحتوي على الصبار وبيروكسيد الهيدروجين وكلوريد سيتيل بيريدينيوم من خلال دراسة إعادة نمو الترسبات لمدة 4 أيام. طرق البحث: تم تقييم درجة الترسبات والعينات اللعابية (اليوم 0 واليوم 4) لعدد 96 مشاركا في تجربة عشوائية منضبطة متوازية الذراع لمدة 4 أيام. تم تقسيم المشاركين إلى خمس مجموعات امتنعت عن تدابير نظافة الفم المعتادة خلال فترة الدراسة واستخدموا غسول الفم المتاح تجاريا والذي يحتوي على الصبار أو بيروكسيد الهيدروجين أو كلوريد سيتيل بيريدينيوم كمنتجات اختبار مع الماء المقطر كعنصر تحكم سلبي وغسول الفم الكلورهيكسيدين كعنصر تحكم إيجابي. تم التعبير عن العد البكتيري اللعابي كوحدات تشكيل مستعمرة (طريقة الاستزراع). النتائج: كان هناك فرق كبير في درجة الترسبات و العد البكتيري اللعابي بين غسولات الفم في اليوم الرابع من الدراسة. كانت درجة الترسبات و العد البكتيري اللعابي لغسول الفم المحتوي على الصبار أقل بكثير من الماء المقطر وأعلى بكثير من غسول الفم الكلورهيكسيدين. كانت درجة الترسبات لغسول الفم المحتوي على بيروكسيد الهيدروجين أعلى بكثير من غسول الفم المحتوي على الصبار وغسول الفم المحتوي على كلوريد سيتيل بيريدينيوم . لم يلاحظ أي فرق بين غسول الفم المحتوي على الصبار و كلوريد سيتيل بيريدينيوم . أيضًا ، العد البكتيري اللعابي لبيروكسيد الهيدروجين كان أعلى من كلوريد سيتيل بيريدينيوم. لم يكن هناك فرق إحصائي بين العد البكتيري اللعابي لغسول الفم المحتوي على الصبار وبيروكسيد الهيدروجين أو الصبار وكلوريد سيتيل بيريدينيوم لم يلاحظ أي فرق للحد من الترسبات و العد البكتيري اللعابي بين غسول الفم المتاح تجاريا المحتوي على الصبار وبيروكسيد الهيدروجين وكلوريد سيتيل بيريدينيوم. الاستنتاجات: كانت الفعالية المضادة للبلاك والمضادة للبكتيريا لغسول الفم المتاح تجاريا المحتوي على الصبار مماثلة لـغسول الفم المحتوي على كلوريد سيتيل بيريدينيوم وأفضل بكثير من غسول الفم المحتوي على بيروكسيد الهيدروجين ومن الممكن أن تكون بديلا طبيعيا لغسول الفم المصنوع كيميائيا. Abstract: Objectives: To evaluate the antiplaque and antibacterial efficacy of commercially available mouthwashes containing aloe vera (AV), hydrogen peroxide (HP), and cetylpyridinium chloride (CPC) in a 4-day plaque regrowth study. Methods: Plaque score and salivary samples were assessed (Day-0 and Day-4) in 96 participants in a randomised, double-blind prospective parallel-arm 4-day plaque regrowth study. Participants were divided into five groups who refrained from engaging in regular oral hygiene measures during the study period and used commercially available mouthwashes containing AV, HP, and CPC as test products with distilled water (DW) and chlorhexidine (CHX) mouthwash as negative and positive controls, respectively. Salivary bacterial count was expressed as colony-forming units (CFU) (culture method). Results: There was a significant difference both in plaque score (p < 0.001) and in CFU (p < 0.001) among the study mouthwashes at Day-4. The plaque score and CFU of AV were significantly higher and lower than those of CHX and DW, respectively. The plaque score of HP was significantly higher than that of AV (p = 0.016) and CPC (p < 0.001). No significant difference was observed between AV and CPC (p = 0.70). Moreover, the CFU of HP was significantly higher than that of CPC (p = 0.04). There was no statistically significant difference between the CFU of mouthwashes containing AV and HP (p = 0.912) or AV and CPC (p = 0.280). No significant difference was seen in the inhibition of plaque and salivary bacterial count between AV, HP, and CPC. Conclusion: The antiplaque and antibacterial efficacy of commercially available AV mouthwash was similar to that of CPC and significantly better than that of HP mouthwash and can be a natural alternative to chemically formulated mouthwashes.